Solving equations
Upcoming SlideShare
Loading in...5
×
 

Solving equations

on

  • 1,465 views

ENTRANCEi.COM and try to set a new standard in the web learning, inspired by the enthusiastic response of our student

ENTRANCEi.COM and try to set a new standard in the web learning, inspired by the enthusiastic response of our student

Statistics

Views

Total Views
1,465
Views on SlideShare
1,465
Embed Views
0

Actions

Likes
0
Downloads
16
Comments
0

0 Embeds 0

No embeds

Accessibility

Categories

Upload Details

Uploaded via as Microsoft PowerPoint

Usage Rights

© All Rights Reserved

Report content

Flagged as inappropriate Flag as inappropriate
Flag as inappropriate

Select your reason for flagging this presentation as inappropriate.

Cancel
  • Full Name Full Name Comment goes here.
    Are you sure you want to
    Your message goes here
    Processing…
Post Comment
Edit your comment

Solving equations Solving equations Presentation Transcript

  • Solving Equations
  • A linear or First degree Equation
    • Eg. 2y+1 = 13
  • 1.Solving linear equations by using inverse operations
    • x – 7 = -3
    • + 7 = +7 (adding 7 on each side)
    • --------------
    • X = 4
  • 3x = 21
    • 3x / 3 = 21 /3 ( dividing each by 3)
    • X = 7
  • Solving Equations with parentheses Solve 3(b+2) +2b = 21
  • 3(b+2) +2b = 21
    • 3b+6 +2b = 21
    • 5b+6 = 21
    • 5b+6-6 = 21-6
    • 5b = 15
    • 5b/5 = 15/ 5
    • Therefore b = 3
  • Solving equation contains fractions m/3 – m/4 = 2
  • m/3 – m/4 = 2
    • 12(m/3) – 12(m/4) = 12(2) [ L.C.M. of 3 &4 is 12)
    • 4m – 3m = 24
    • So, m= 24
  • Solving Equations by cross multiplying
    • If x / 3 = (x + 4)/5 , what is the value of x?
  • If x / 3 = (x + 4)/5 , what is the value of x?
    • 5(x) = 3(x+4)
    • 5x = 3x +12
    • 2x = 12
    • x = 12 / 2
    • Therefore x= 6
  • Using A root of an equation to answer a question
    • If 3y – 2 = 4 , what is the value of y – 2 ?
  • If 3y – 2 = 4 , what is the value of y – 2 ?
    • If 3y – 2 = 4 ,then 3y = 6
    • Therefore y = 2
    • The value of y-2 = 2 – 2 = 0
  • The END